O método cognitivo-histórico e o ensino de física mediado por epistemologias - Cauduro, Paola Jardim (2017)
The latest data from Brazilian education have shown that in recent years, although there has been a slight improvement in the infrastructure offered to schools, much still needs to be done to ensure better conditions, especially for students in public schools. This reality is even more pronounced when it comes to localized schools or when students come from areas of social vulnerability, which for many authors constitutes the factor that contributes to poor performance and school dropout. The high levels of disapproval and drop-out rates registered in recent years in Rio Grande do Sul, for all socioeconomic levels, led the Secretária de Educação (SEDUC) to rethink the way in which secondary education was being administered, thus instituting Ensino Médio Politécnico in 2012, as a differentiated proposal and according to the other documents of the Brazilian education. With this in mind, the Cognitive-Historical Method (MCH) proposed by Nersessian (2008) was presented as a theoretical reference for presenting tools that allow students to understand scientific processes through the history and attitudes of their own authors, increasing the quality of his scientific thinking, the use of reasoning and the development of his own operational methodologies in various interactions in physics classes. In addition, the materials developed through the Explicit Teaching approach were developed, which favors the development of cognitive abilities in students, fully based on cognitive psychology and already proven in several studies. The methodology of data collection chosen for this research was the experimental model Solomon Four - Group Design, where the intervention based on the MCH had a well defined protocol: pre-test consisting of two questions with daily situations; the intervention composed of text about life, career, historical and social context, crucial experiments of scientists chosen according to fundamental concepts studied by them, explanation of concepts, examples, problems and by a practical activity, with script, related to the studied scientist; each scientist's post-test consists of five multiple-choice questions. The results of this work made it possible to answer that the MCH is a tool that proved to be effective in the implementations in a school located in the central-western administrative region of the city of Santa Maria - RS for the contents of Temperature, Heat and Thermometric Scales; Isothermal Transformation; Ohm Laws and Electric Generators. On explicit teaching and learning management, most of the constituent items could be realized with high success level. However, the items ensuring a high success rate, checking for understanding and differentiating otherwise need further improvement. These items are most often related to students who miss consecutive classes, which end up interfering with their learning because the class has advanced and they do not. To solve this problem it is necessary to develop strategies that favor the recovery of unrealized activities.